Implementation of a Bundled Consent Process in the ICU: A Single-Center Experience*. Issue 10 (October 2019) - Anandaiah, Asha M.; Stevens, Jennifer P.; Sullivan, Amy M.
Abstract : Objectives: A bundled consent process, where patients or surrogates provide consent for all commonly performed procedures on a single form at the time of ICU admission, has been advocated as a method for improving both rates of documented consent and patient/family satisfaction, but there has been little published literature about the use of bundled consent. We sought to determine how residents in an academic medical center with a required bundled consent process actually obtain consent and how they perceive the overall value, efficacy, and effects on families of this approach. Design: Single-center survey study. Setting: Medical ICUs in an urban academic medical center. Subjects: Internal medicine residents. Interventions: We administered an online survey about bundled consent use to all residents. Quantitative and qualitative data were analyzed. Measurements and Main Results: One-hundred two of 164 internal medicine residents (62%) completed the survey. A majority of residents (55%) reported grouping procedures and discussing general risks and benefits; 11% reported conducting a complete informed consent discussion for each procedure. Respondents were divided in their perception of the value of bundled consent, but most (78%) felt it scared or stressed families. A minority (26%) felt confident that they obtained valid informed consent for critical care procedures with the use of bundled consent. An additional theme that emerged from qualitative data was concern regarding the validity of anticipatory consent. Conclusions: Resident physicians experienced with the use of bundled consent in the ICU held variable perceptions of its value but raised concerns about the effect on families and the validity of consent obtained with this strategy. Further studies are necessary to further explore what constitutes best practice for informed consent in critical care. Abstract : Supplemental Digital Content is available in the text.